’n Nuwe lewe: Olga Kirsch se studentegedig “Resurrexit” / A New Life: Olga Kirsch’s Student Poem “Resurrexit” - Minnaar, Thomas; Roth, Egonne (Werkwinkel, 2014)
The poem “Resurrexit” published by Olga Kirsch in 1945 in the student paper WU´s VIEWS has been all but forgotten. It is, however, a beautiful and an important poem with a pantheistic character. It commemorates the death of the young Jewish flight navigator lieutenant Alec Medalie, whose fighter plane was shot down by German antiaircraft fire near the Yugoslavian coast in 1944. Psychoanalysis opens the poem up to a reading which turns the typical male symbolic order’s death and men’s chaos caused by war into the young man’s rebirth as a new form of being. This happens through the maternal earth’s uterine sea. The fallen is absorbed by the sea and after a period taken up into the clouds to return to the mother and the earth, albeit in a new form. The concept of the chora plays a part in this resurrection which offers consolation to all who are subject to the inevitable uncertainty of the human condition and those who stay behind after a sudden death.